Surface etching and silane heating using Er:YAG and Nd:YAG lasers in dental ceramic luted to human dentin - Feitosa, Fernanda A. [UNESP]; Tribst, João P. M. [UNESP]; Araújo, Rodrigo M. [UNESP]; Pucci, César R. [UNESP] (Wiley, 2021)
Investigate the tensile bond strength, surface morphology, and wettability of reinforced glass-ceramic etched with high power laser at different protocols and luted to human dentin. Fifty carious-free human molars were used in this study and distributed in five groups according to surface etching: (Control [HF10% + Silane]; Er [Er:YAG + Silane]; Sil + Er [Silane + Er:YAG]; Nd [Nd:YAG + Silane]; and Nd + Sil [Silane + Nd:YAG]). After, the tensile bond strength test was performed. Three specimens per group were used to perform the surface morphologies by using scanning electron microscopy analysis and wettability by using the sessile drop technique. Failure modes were determined. Data were analyzed with two-way analysis of variance and Tukey tests, with α =.05. The bond strength data showed statistically significant differences among tested groups for the laser and silanization technique type (p <.001). The highest calculated bond strength values were obtained with Er (19.25 ± 3.70 MPa) followed by Sil + Er (14.11 ± 4.11 MPa), Control (9.42 ± 2.27 MPa), Nd (9.66 ± 2.02 MPa), and Nd + Sil (6.71 ± 1.88 MPa), respectively. The silane application prior to the laser irradiation showed an inferior bond strength compared to the conventional silanization technique. The surface etching using Er:YAG laser showed promissor results for the lithium disilicate.
Keywords: bond strength; ceramics; dental materials; Er:YAG laser; Nd:YAG laser